Inspiratory pressure support prolongs exercise induced lactataemia in severe COPD. Issue 7 (1st July 2000) - Polkey, Michael I; Hawkins, Peter; Kyroussis, Dimitris; Ellum, Sheric G; Sherwood, Roy; Moxham, John
Abstract : BACKGROUND: A physiological benefit from pulmonary rehabilitation in chronic obstructive pulmonary disease (COPD) is more probable if exercise is performed above the lactate threshold. This study was undertaken to investigate whether it was possible to extend the lactataemia of exercise using non-invasive inspiratory pressure support (IPS). METHODS: Plasma lactate levels were measured in eight men with severe COPD who performed two treadmill walks at an identical constant work rate to a condition of severe dyspnoea; the second walk was supported by IPS. RESULTS: Mean plasma lactate levels before the free and IPS assisted walks were 1.65 mmol/l and 1.53 mmol/l, respectively (p = NS). Lactate levels increased during both walks to 2.96 mmol/l and 2.42 mmol/l, respectively (p = 0.01 for each) but the duration of the IPS assisted walk was significantly greater than the free walk (13.6 minutes versus 5.5 minutes, p = 0.01). CONCLUSIONS: Patients with severe COPD can sustain exercise induced lactataemia for longer if assisted with IPS. This technique may prove to be a useful adjunct in pulmonary rehabilitation.